A new species of Trembleya (Melastomataceae: Microlicieae) with notes on leaf anatomy and generic circumscription - Pacifico, Ricardo; Almeda, Frank; Do Carmo, Amanda Aparecida; Fidanza, Karina (Phytotaxa, 2019)
A new species of Trembleya that was first recognized by Auguste François Marie Glaziou is described. Line drawings, photographs, descriptions of the leaf anatomical structure, SEM images, distribution maps, conservation status, and comments on the generic circumscription of Trembleya are provided. The new species appears to be endemic to the Chapada dos Veadeiros in Goiás, Brazil. It is characterized by its oblong-lanceolate leaf blades (1.4–4.5 × 0.3–0.9 cm) that are papyraceous, 3–5-nerved from the base and glandular-punctate on both surfaces, tertiary veins not evident, well-developed inflorescences, flowers with subisomorphic stamens that are completely yellow and ovaries with 3(–4) locules. A conservation assessment of Endangered (EN) is recommended for this species based on IUCN Red List Categories and Criteria.